Social Solidarity Economy Conceptual framework and call for accreditation - حسين, احمد خلف (Journal of Legal Sciences, 2019)
In this study, we sought to identify in detail all that relates to the social and solidarity economy in terms of its foundation, including historical development, philosophical basis, legalization and its associated concepts, characteristics, objectives, elements and obstacles, especially after the ways of achieving social justice attracted several individual, socialist and Islamic philosophies , Each seeks to understand them in different ways and methods while denying the means and methods of other philosophies in this framework, emerged some of the tools that may have received the consensus of the theoreticians and supporters of all those ideologies, namely, social responsibility and cooperative insurance and cooperatives and other This is a focus on Iraq as it represents a fertile medium for the growth and growth of these applications, especially the primitive ones, which were and still are spreading and expand to reach the non-traditional economic actors such as women and my family And enable them to contribute strongly to economic activity to realize social justice and to promote new, alternative and innovative financing instruments and access to the real economy that seeks to produce goods and services and meet the needs of people. Da for the goal of achieving the maximum profit.